Boosting in English and Indonesian Research Articles: A Cross-Cultural and Cross-Disciplinary Study - I Nyoman Suka Sanjaya (Bina Nusantara University, 2016)
Boosters, defined as linguistic devices (e.g. certainly) used by writers to indicate full commitment to the truth value of a proposition, has received little attention from applied linguists, despite their persuasive power in research writing. The present study investigated the effects of the two variables of sociocultural context and discipline on the frequency of use of boosters in research articles. A specialized corpus of 104 research articles published between 2007 and 2010 taken from applied linguistics and chemistry written in English and Indonesian by the respective native speaker scholars were quantitatively analyzed using 2 x 2 Factorial ANOVA. The results showed that there was a significant main effect of sociocultural context, F (1, 100) = 44,34, p <0,05, ŋ2 = 0,307, a significant main effect of discipline, F (1,100) = 19,16, p < 0,05, ŋ2 = 0,161, and a significant interaction between sociocultural context and discipline, F (1,100) = 6,90, p < 0,05, ŋ2 = 0,065. However, the within-sociocultural context simple effects analysis revealed that English applied linguistics and chemistry research articles were not significantly different from each other, F (1,101) = 1,07, n.s. suggesting that, discipline might not be a decisive factor that influences boosting usage in research articles. These results indicate that the two variables (sociocultural context and discipline) exerted unequal influence upon boosting practices in research articles. The differential characteristics of the two sociocultural contexts are offered as explanations to account for the differential boosting practices of English and Indonesian research articles.